الدراسات الثقافية والنقد الثقافي - بوزكري, آمال; رقيق, ميلود (جامعة الوادي - University of Eloued, 2022)
تعد الدراسات الثقافية منذ ظهورها من القضايا والإشكالات البارزة التي شغلت الساحة النقدية، باعتبارها ثورة فعلية منهجية على المناهج النقدية الأدبية التقليدية وعلى الخطاب الفني الأدبي؛ لطرحها المابعد حداثي حيث ساهمت في ظهور العديد من الخطابات الهامشية المضادة للخطاب المركزي، من بين هذه الخطابات النقد الثقافي، والذي يعد من أبرز ما أفرزته النظرية النقدية المعاصرة، بما تحمله من آراء نقدية، لذلك اقتحمت الساحة النقدية الأدبية، كما استحوذت على توجه النقاد. خلال هذه الورقة البحثية سنلقي الضوء على الإطار النظري المفاهيمي للدراسات الثقافية والنقد الثقافي، فيتبنى بحثنا جملة من الأهداف لبناء إطار منهجي معرفي متكامل بين النقد الثقافي والدراسات الثقافية محاولين رفع اللثام عن المرجعيات والمفاهيم الأساسية لهذا المجال وذلك بالإجابة على إشكاليات البحث: كيف نشأت الدراسات الثقافية؟ ما دور مدرسة بيرمنجهام في تطورها؟ كيف تم ظهور النقد الثقافي؟ ما هي آلياته؟ Abstract: Cultural studies, since their emergence, have been prominent issues and problems that have occupied the critical arena, as a systematic real revolution on traditional literary monetary curricula and on literary artistic discourse; For its post-modernist presentation, it contributed to the emergence of many marginal anti-central discourse speeches, among them cultural criticism, which is one of the highlights of contemporary monetary theory, with its views, so it stormed the literary monetary arena and captured the orientation of critics. During this paper, we will look at the conceptual theoretical framework for cultural studies and criticism. Our research adopts a number of objectives to build an integrated methodological and cognitive framework between cultural criticism and cultural studies, trying to detect the basic references and concepts in this area by answering the problems of research: How did cultural studies arise? What is the role of Birmingham School in its development? How has cultural criticism emerged? What are its mechanisms? Keywords: cultural studies, cultural criticism, conscience, center, margin, format, culture.
the Cultural Studies And Cultural Criticism
مقال
Keywords: الدراسات الثقافية؛ ; النقد الثقافي؛ ; المضمر؛ ; المركز؛ ; الهامش؛ ; النسق; cultural studies; cultural criticism ; implicit ; center; margin ; format